The Dynamics of Gender Stereotype Depicted by Othello and Desdemona in Othello The Film - Nushrotin Rofiqoh (2011)
This study examines the dynamics of gender stereotype depicted by the main characters in the film version of Shakespeare’s Othello, Othello the film. The main characters, Othello and Desdemona, depict different gender presentation compared to the first portrayal in the beginning of the movie. Thus, the main concern of this study is to fully explore the depiction of the characters of Othello and Desdemona in Othello the film from gender perspective and also to explain the presentation of the shifts in gender presentation of both characters in Othello the film. The changes are constructed through the binary opposition of masculinity and femininity. The theory of gender stereotype by Deaux and Lewis is used in analysing the shifts of gender stereotype in the film. The study sums up that there are dynamics of gender stereotype depicted by the Othello and Desdemona in Othello the film. It is also found that love, trust, and race are the big causes of the dynamics of gender stereotype in this film, and Othello as a Moor is not considered as a “true man.”